The 6Li/7Li isotopic ratio in the metal-poor binary CS22876-032 - González Hernández, Jonay I.; Bonifacio, Piercarlo; Caffau, Elisabetta; Ludwig, Hans-Günter; Steffen, Matthias; Monaco, L.; Cayrel, R. (Astronomy and astrophysics, 2019)
Aims. We present high-resolution and high-quality UVES spectroscopic data of the metal-poor double-lined spectroscopic binary CS 22876-032 ([Fe/H] approximately −3.7 dex). Our goal is to derive the 6Li/7Li isotopic ratio by analysing the Li I λ 670.8 nm doublet.Methods. We co-added all 28 useful spectra normalised and corrected for radial velocity to the rest frame of the primary star. We fitted the Li profile with a grid of the 3D non-local thermodynamic equilibrium (NLTE) synthetic spectra to take into account the line profile asymmetries induced by stellar convection, and performed Monte Carlo simulations to evaluate the uncertainty of the fit of the Li line profile.Results. We checked that the veiling factor does not affect the derived isotopic ratio, 6Li/7Li, and only modifies the Li abundance, A(Li), by about 0.15 dex. The best fit of the Li profile of the primary star provides A(Li) = 2.17 ± 0.01 dex and 6Li/7Li % at 68% confidence level. In addition, we improved the Li abundance of the secondary star at A(Li) = 1.55 ± 0.04 dex, which is about 0.6 dex lower than that of the primary star. Conclusions. The analysis of the Li profile of the primary star is consistent with no detection of 6Li and provides an upper limit to the isotopic ratio of 6Li/7Li < 10% at this very low metallicity, about 0.5 dex lower in metallicity than previous attempts for detection of 6Li in extremely metal poor stars. These results do not solve or worsen the cosmological 7Li problem, nor do they support the need for non-standard 6Li production in the early Universe.
Im Text sind "6" und "7" hochgestellt
Gesehen am 12.05.2021